2000
DOI: 10.1177/146642400012000113
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual knowledge and practices amongst secondary school girls in lle lfe, Nigeria

Abstract: The menstrual knowledge and practices of 352 randomly selected healthy Nigerian schoolgirls were studied. 187 (53.1%) had attained menarche. 40% of subjects were deficient in knowledge about menstruation. Although menstrual knowledge was higher in post-menarcheal girls, 10% of these were totally ignorant about menses and 84% were not psychologically prepared for the first menses. Girls' menstrual knowledge was positively associated with parental education. The major source of menstrual information was the fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
9
31
2
Order By: Relevance
“…This is not surprising, as a higher proportion of the daughters attended formal schools with strong peer influence. A lower figure was reported among secondary school students in Ile-Ife, southwest Nigeria (33.7%; Abioye-Kuteyi, 2000), while in Nepal almost all respondents (94%) used sanitary pads (Adhikari, Kadel, Dhungel, & Mandal, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…This is not surprising, as a higher proportion of the daughters attended formal schools with strong peer influence. A lower figure was reported among secondary school students in Ile-Ife, southwest Nigeria (33.7%; Abioye-Kuteyi, 2000), while in Nepal almost all respondents (94%) used sanitary pads (Adhikari, Kadel, Dhungel, & Mandal, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…This was similar to findings of a study conducted by AbioyeKuteyi and Adinma et al in Onitsha Nigeria that revealed that unsanitary absorbent materials were used during menses. 27,9 This findings might be due to high level of poverty in this environment as majority of the respondents' parents and guidians were not gainfully employed. Good menstrual hygiene practice include safe and sanitary disposal of absorbent materials used during menses.…”
Section: Discussionmentioning
confidence: 95%
“…The correspondence of increased absence with pubertal age should also be considered. Although onset of menarche is generally assumed to have an impact on educational outcomes (Abioye-Kuteyi, 2000;Ali and Rizvi, 2009;Scott et al, 2009;Sommer, 2009), studies which have documented this relationship have found conflicting results. A randomized trial in Nepal providing re-usable menstrual cups found that girls receiving the intervention were no more likely than their counterparts to attend school during their periods; however, the authors did not consider availability of water and sanitation in their trial (Oster and Thornton, 2010).…”
Section: Discussionmentioning
confidence: 95%